FMRI correlates of olfactory processing in typically-developing school-aged children. (30th January 2019) - Kleinhans, Natalia M.; Reilly, Melissa; Blake, Matthew; Greco, Gabriella; Sweigert, Julia; Davis, Greg E.; Velasquez, Francisco; Reitz, Fredrick; Shusterman, Dennis; Dager, Stephen R.
Highlights: Olfactory fMRI activation is robust in school-aged children. Our respiratory-synchronized odor stimulation task is fast and clinically feasible. Olfactory fMRI activation reflects individual differences in ability to detect odors. Abstract: Human olfactory processing is understudied relative to other sensory modalities, despite its links to neurodevelopmental and neurodegenerative disorders. To address this limitation, we developed a fast, robust fMRI odor paradigm that is appropriate for all ages and levels of cognitive functioning. To test this approach, thirty-four typically developing children aged 7–12 underwent fMRI during brief, repeated exposure to phenylethyl alcohol, a flower-scented odor. Prior to fMRI scanning, olfactory testing (odor detection and identification) was conducted. During fMRI stimulus presentation, odorant release was synchronized to each participant's inspiratory phase to ensure participants were inhaling during the odorant exposure. Between group differences and correlations between activation and odor detection threshold scores were tested using the FMRIB Software Library. Results demonstrated that our 2-min paradigm significantly activated primary and secondary olfactory regions. In addition, a significant relationship between odor detection threshold and higher activation in the right amygdala and lower activation in the left frontal, insular, occipital, and cerebellar regions was observed, suggesting that this approach is sensitive to individual differences in olfactory processing. These findings demonstrate the feasibility of studying olfactory function in children using brain imaging techniques.